Association between cholesterol efflux capacity and peripheral artery disease in coronary heart disease patients with and without type 2 diabetes: from the CORDIOPREV study - Elena M. Yubero-Serrano; Juan F. Alcalá-Diaz; Francisco M. Gutierrez-Mariscal; Antonio P. Arenas-de Larriva; Patricia J. Peña-Orihuela; Ruth Blanco-Rojo; Javier Martinez-Botas; Jose D. Torres-Peña; Pablo Perez-Martinez; Jose M. Ordovas; Javier Delgado-Lista; Diego Gómez-Coronado; et al. (Cardiovascular Diabetology, 2021)
Abstract Background Peripheral artery disease (PAD) is recognized as a significant predictor of mortality and adverse cardiovascular outcomes in patients with coronary heart disease (CHD). In fact, coexisting PAD and CHD is strongly associated with a greater coronary event recurrence compared with either one of them alone. High-density lipoprotein (HDL)-mediated cholesterol efflux capacity (CEC) is found to be inversely associated with an increased risk of incident CHD. However, this association is not established in patients with PAD in the context of secondary prevention. In this sense, our main aim was to evaluate the association between CEC and PAD in patients with CHD and whether the concurrent presence of PAD and T2DM influences this association. Methods CHD patients (n = 1002) from the CORDIOPREV study were classified according to the presence or absence of PAD (ankle-brachial index, ABI ≤ 0.9 and ABI > 0.9 and < 1.4, respectively) and T2DM status. CEC was quantified by incubation of cholesterol-loaded THP-1 cells with the participants' apoB-depleted plasma was performed. Results The presence of PAD determined low CEC in non-T2DM and newly-diagnosed T2DM patients. Coexisting PAD and newly-diagnosed T2DM provided and additive effect providing an impaired CEC compared to non-T2DM patients with PAD. In established T2DM patients, the presence of PAD did not determine differences in CEC, compared to those without PAD, which may be restored by glucose-lowering treatment. Conclusions Our findings suggest an inverse relationship between CEC and PAD in CHD patients. These results support the importance of identifying underlying mechanisms of PAD, in the context of secondary prevention, that provide potential therapeutic targets, that is the case of CEC, and establishing strategies to prevent or reduce the high risk of cardiovascular events of these patients. Trial registration https://clinicaltrials.gov/ct2/show/NCT00924937 . Unique Identifier: NCT00924937